PERDAGANGAN ANAK (CHILD TRAFFICKING) SEBAGAI KEJAHATAN TRANSNASIONAL DAN KAITANNYA DENGAN GLOBALISASI - Fahmi, Teuku (JURNAL SOSIOLOGI, 2013)
This paper reviews the issue of child trafficking as a transnational crime is also related to globalization. By browsing a variety of documents and books related to child trafficking, this paper gives an overview of the humanitarian issues for the global and local level. In the end, child trafficking is happening in various parts of the world have threatened the existence of human dignity and the future of child endangering.